Laws of Ratification of an International Treaty in Indonesian Laws Hierarchy - Sidharta, Noor (The Constitutional Court of the Republic of Indonesia, 2017)
This journal article discusses the laws of ratification of an international treaty in Indonesian laws hierarchy. This journal uses a normative research approach where a draft agreement and laws are used as primary data apart from the laws and international treaties. There are some issues that still unsettled related to the legal status of the laws of ratification of an international treaty that have impacts in the implementation of the treaty. The laws of ratification of an international treaty now is still classified as general laws whose the content of the norm has been discussed by the Peopleâs Representatives Council, therefore the laws of ratification of an international treaty automatically become the object of Judicial Review at the Constitutional Court of the Republic of Indonesia. The cancellation of the laws of ratification of an international treaty impacts the cancellation of the deal on the treaty and it has failed the pacta sunt servanda principle, which becomes the basis of a treaty. To solve problems related to the cancellation of laws of ratification of an international treaty at the Constitutional Court, there are several efforts on state administration by classifying the laws which differ the general laws from the laws whose contents are related to the international treaty. Furthermore, a progressive new method on the state administration is needed by giving a Judicial Preview right to the Constitutional Court to conduct a review on the bill of the ratification of an international treaty based on its suitability to the constitution.